Comparison of salivary collection and processing methods for quantitative HHV-8 detection - Speicher, DJ; Johnson, NW (Oral diseases, 2014)
Objectives Saliva is a proved diagnostic fluid for the qualitative detection of infectious agents, but the accuracy of viral load determinations is unknown. Stabilising fluids impede nucleic acid degradation, compared with collection onto ice and then freezing, and we have shown that the DNA Genotek P‐021 prototype kit (P‐021) can produce high‐quality DNA after 14 months of storage at room temperature. Here we evaluate the quantitative capability of 10 collection/processing methods. Methods Unstimulated whole mouth fluid was spiked with a mixture of HHV‐8 cloned constructs, 10‐fold serial dilutions were produced, and samples were extracted and then examined with quantitative PCR (qPCR). Calibration curves were compared by linear regression and qPCR dynamics. Results All methods extracted with commercial spin columns produced linear calibration curves with large dynamic range and gave accurate viral loads. Ethanol precipitation of the P‐021 does not produce a linear standard curve, and virus is lost in the cell pellet. DNA extractions from the P‐021 using commercial spin columns produced linear standard curves with wide dynamic range and excellent limit of detection. Conclusion When extracted with spin columns, the P‐021 enables accurate viral loads down to 23 copies μl−1 DNA. The quantitative and long‐term storage capability of this system makes it ideal for study of salivary DNA viruses in resource‐poor settings.